L-Leucine Templated Biomimetic Assembly of SnO2 Nanoparticles and Their Lithium Storage Properties. (19th August 2018) - Yu, Peng; Liu, Mili; Gong, Haixiong; Wu, Fangfang; Yi, Zili; Liu, Hui
Abstract : SnO2 nanoparticles have been synthesized by a novel route of a sol-gel method assisted with biomimetic assembly using L-leucine as a biotemplate. The microstructure of as-prepared SnO2 nanoparticles was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), Fourier transform infrared spectra (FT-IR), and Brunner−Emmet−Teller (BET) measurements. The results demonstrated that the growth of SnO2 could be regulated by L-leucine at a high calcination temperature. The electrochemical performance of SnO2 was also measured as anodes for lithium-ion battery. It is a guidance for the growth regulation of SnO2 at high temperature to obtain SnO2 /C with nanosized SnO2 coated by a graphitic carbon.